Exploring the relationship between vitamin D deficiency and comorbid heart disease in Americans with mood disorders: a cross-sectional nationwide study - Habib, Maleeha; Jaka, Sanobar; Pokhrel, Sandesh; Sejdiu, Albulena; Patel, Archna; Vashist, Sreshatha; Arisoyin, Abimbola; Pathak, Meenal; Bachu, Anil K.; Rajaram Manoharan, Senthil Vel Rajan; Mogallapu, Raja; Patel, Rikinkumar S. (Frontiers in Psychiatry, 2023)
Objective This study aimed to explore the relationship between vitamin D deficiency and comorbid heart disease in adult inpatients with mood disorders (depressive and bipolar disorders). Methods A cross-sectional investigation was carried out employing the nationwide inpatient dataset, which encompassed 910,561 adult inpatients aged 18 to 50 years diagnosed with depressive and bipolar disorders. Additionally, the sample was categorized based on the presence of comorbid heart disease. We utilized a logistic regression model to assess the odds ratio (OR), pertaining to demographic features and coexisting medical conditions in relation to comorbid heart disease. Results Comorbid heart disease was present in 1.3% of inpatients with mood disorders; they were middle-aged (mean age 42.7 years) men and White individuals. Inpatients with depressive disorder had a higher risk of comorbid heart disease (OR 1.19, 95% CI 1.15–1.24) compared to those with bipolar disorders. Inpatients with comorbid heart disease had a higher prevalence of medical and psychiatric comorbidities. The prevalence of vitamin D deficiency was 2.3% in mood disorders but higher in those with comorbid heart disease (2.9%). Vitamin D deficiency showed a notable correlation with comorbid heart disease, resulting in a 26% increased risk in the unadjusted regression model (OR 1.26, 95% CI 1.13–1.40). However, after accounting for potential confounding factors, including comorbidities, the risk did not exhibit statistical significance (OR 1.08, 95% CI 0.97–1.21). Among psychiatric comorbidities, trauma-related (OR 1.22, 95% CI 1.17–1.28) and tobacco-related (OR 1.31, 95% CI 1.26–1.37) disorders had a higher risk of association with comorbid heart disease. Conclusion Middle-aged men with depressive disorders and from low-income families had a higher risk of developing comorbid heart disease. Trauma-related and tobacco-related disorders were associated with an increased risk by 20–30% for comorbid heart disease in inpatients with mood disorders. Vitamin D deficiency was not associated with the risk of comorbid heart disease after controlling demographics and comorbid cardiovascular risk factors.